2019
DOI: 10.1089/dia.2019.0234
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data from the First U.S. Commercial Users of an Implantable Continuous Glucose Sensor

Abstract: Background: The Eversense Ò Continuous Glucose Monitoring (CGM) System, with the first 90-day implantable sensor, received FDA (Food and Drug Administration) approval in June 2018. No real-world experience has been published. Methods: Deidentified sensor glucose (SG) data from August 1, 2018 to May 11, 2019 in the Eversense Data Management System (DMS) were analyzed for the first 205 patients who reached a 90-day wear period on the Eversense CGM system. The mean SG, standard deviation (SD), median interquartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…The CGM system is designed to replace finger stick blood glucose testing for diabetes treatment decisions. 9,30,43,66-73…”
Section: Real-time Cgm Systems That Are Implanted Long-term Within Thmentioning
confidence: 99%
“…The CGM system is designed to replace finger stick blood glucose testing for diabetes treatment decisions. 9,30,43,66-73…”
Section: Real-time Cgm Systems That Are Implanted Long-term Within Thmentioning
confidence: 99%
“…2,[20][21][22] Using de-identified glucose data (Eversense LTI CGM) from the Eversense data management system, Sanchez et al found that the percentage of sensor glucose readings at <54 mg/dL was 1.2%, <70 mg/dL was 4.1%, time in normal glycemic range (70-180 mg/dL) was 62.3%, >180-250 mg/dL was 21.9%, and > 250 mg/dL was 11.6% at 90 days. 23 The median transmitter wear time in this analysis utilizing postmarketing data was 83.6%. 23 This real-world analysis suggests that the Eversense LTI CGM may provide similar benefits to isCGM and conventional rtCGM, although additional comparative efficacy analysis is lacking at this time.…”
Section: Glycemic Efficacymentioning
confidence: 79%
“…23 This real-world analysis suggests that the Eversense LTI CGM may provide similar benefits to isCGM and conventional rtCGM, although additional comparative efficacy analysis is lacking at this time. 23 However, there are several ongoing clinical trials designed to further evaluate the glycemic efficacy of the Eversense LTI CGM ( Table 2). 24…”
Section: Glycemic Efficacymentioning
confidence: 95%
“…Identifying and eliminating tape allergens is important to ensure comfortable use of devices and enhance patient adherence (102-105). In some instances, use of an implanted sensor can help avoid skin reactions in those who are sensitive to tape (106,107 (108,109), although inhaled insulin is also available. Others use insulin pumps or automated insulin delivery devices (see sections on those topics below).…”
Section: Side Effects Of Cgm Devicesmentioning
confidence: 99%